2003
DOI: 10.1118/1.1631915
|View full text |Cite|
|
Sign up to set email alerts
|

Boron neutron capture therapy of skin melanomas at the RA-6 reactor: A procedural approach to beam set up and performance evaluation for upcoming clinical trials

Abstract: This article reports on the progress of the modeling and experimental characterization of the RA-6 reactor neutron beam, designed for the upcoming BNCT clinical trials of skin melanoma, and presents the first theoretical analysis of such beam performance. The aspects relating to surface source modeling and assessment, beam dosimetry, treatment planning system calibration, and treatment planning optimization are presented herein. Several methods and criteria were established in order to provide guidance for fut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…The data measured by CAB in this phantom are used to benchmark the treatment planning software NCTPlan utilized by the CNEA for dose calculations. 5 Examining the calibrated output from NCT-Plan enabled a quantitative comparison between the dose prescribed by CNEA to that measured and so prescribed by MIT for the four individual dose components including that from thermal neutron capture in boron. A fourth-order polynomial was fit using the least-squares method to the MIT dose measurements and the CNEA NCTPlan calculation was TABLE I.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data measured by CAB in this phantom are used to benchmark the treatment planning software NCTPlan utilized by the CNEA for dose calculations. 5 Examining the calibrated output from NCT-Plan enabled a quantitative comparison between the dose prescribed by CNEA to that measured and so prescribed by MIT for the four individual dose components including that from thermal neutron capture in boron. A fourth-order polynomial was fit using the least-squares method to the MIT dose measurements and the CNEA NCTPlan calculation was TABLE I.…”
Section: Resultsmentioning
confidence: 99%
“…Although identical ionization chambers are employed, the two groups convert ionization response to absorbed dose differently. The CAB group empirically determines the thermal neutron sensitivities of each chamber 5,7 and subtracts a scaled response from each measurement based upon the measured thermal neutron fluence to then determine the photon and fast neutron doses from the residual ionization currents as initially proposed by Rogus et al 8 The MIT group, however, now includes the thermal neutron response as part of the neutron sensitivity of each chamber and determines the dose from neutrons of all energies. 9 To complete the intercomparison, CNEA computed a treatment plan using the Monte Carlo based NCTPlan ordinarily used for dose calculations in their clinical trials.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of this fact has encouraged our group to improve the computational dosimetry of our patients, continuously progressing towards a more accurate modeling of the dose distribution. [10][11][12] In this context, DIRI became an option to study, non-invasively, the evolution of normal tissue reactions and melanoma control. Together with clinical observation, computed tomography scans and high resolution Doppler ultrasound, DIRI was employed before and after the treatment of melanoma patients with BNCT.…”
Section: Bnct For Malignant Melanomamentioning
confidence: 99%
“…planned to enroll 30 melanoma patients for a clinical trial, and they reported the first results of BNCT for the treatment of melanoma. For the first patient, they administered BPA-F at 14 g/m 2 for more than 1.5 h, based on the area of the skin at the affected area ( 94 , 95 ). Results showed that 19 of the 25 nodules were complete response (CR) within 4 weeks of BNCT treatment.…”
Section: Clinical Trials With Boron Delivery Agentsmentioning
confidence: 99%